Peningkatan Employee Engagement Calon Pegawai Negeri Sipil Fakultas Ushuluddin, Adab, dan Dakwah IAIN Pontianak Melalui Penerapan The 7 Islamic Daily Habits - Warohmah, Hizzatul; Sukmawati, Fitri; Amalia, Kiki; Hefni, Harjani; Sophian, Muhammad (Universitas Islam Negeri K.H. Abdurrahman Wahid Pekalongan, 2023)
This study aims to analyze the influence of the implementation of The 7 Islamic Daily Habits training on prospective civil servants at the ushuluddin adab and da'wah faculties of the Pontianak State Islamic Institute and analyze how much influence this has on the experimental group. This research is a quantitative research with a true experimental research design which has two types of groups, namely the treated group and the non-treated group which is analyzed using the Wilcoxon Matched Pairs test. Data collection techniques used by researchers in the form of measurement scales, interview and observation techniques. The results of this study indicate that the research hypothesis (Ha) in the experimental group was accepted with a result of 0.028 (p ≤ 0.05). Therefore, this study had an effect on subjects in increasing employee engagement of prospective civil servants at the Ushuluddin Adab Faculty and Da'wah Pontianak State Islamic Institute, while the results for the control group were not significant or rejected with a score of 0.109.